Antifungal and cytotoxic activities of extracts obtained from underutilised edible tropical fruits - Ong, Cheong Wei; Chan, Yik Sin; Khoo, Kong Soo; Ong, Hean Chooi; Sit, Nam Weng (Wolters Kluwer Medknow Publications, 2018)
Objective: To evaluate antifungal and cytotoxic activities of four underutilised fruit species, i.e. Artocarpus altilis (breadfruit), Cynometra cauliflora (nam-nam), Mangifera pajang (M. pajang) (Bambangan) and Physalis minima (wild gooseberry). Methods: Extracts from the fresh flesh of Artocarpus altilis and Cynometra cauliflora, the flesh and kernel of M. pajang, and the whole fruit of Physalis minima were obtained by sequential extraction using hexane, chloroform, ethyl acetate, ethanol, methanol and distilled water. Each extract was assessed against six species of human fungal pathogens using a colourimetric broth microdilution method. The cytotoxicity was evaluated using African monkey kidney epithelial (Vero) cells. Results: All 30 extracts showed inhibitory activity against Cryptococcus neoformans. However, none of the extracts were active against Aspergillus fumigatus. The ethanol, methanol and water extracts from the kernel of M. pajang fruit showed the strongest activity against three species of Candida and Trichophyton interdigitale, with a minimum inhibitory concentration range of 0.001 - 0.630 mg/mL. The corresponding mean 50% cytotoxic concentrations for these three extracts were 358.7, 158.4 and 261.3 μg/mL, respectively against Vero cells. In contrast, the flesh of M. pajang fruit (hexane, chloroform and ethyl acetate extracts) showed statistically significant (P<0.001; ANOVA) strong toxicity against the cells, with 30.6, 13.5 and 22.2 μg/mL of mean values of 50% cytotoxic concentrations, respectively. Conclusions: The results suggest that the bioactivity of the kernel of M. pajang fruit is more selective towards fungi and thus is a potential source of new antifungal agents.